Ina- Manggagawa- Mag-aaral: The Lived Experiences, Challenges, Coping and Aspirations of Working- Student- Mothers - Sudweste, Jennie Marie V.; Jumamil, Ana Nelia L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Many individuals are pursuing graduate degrees while working and raising children. The aim of this study is to explore the lived experiences, challenges, coping, and aspirations of working-student- mothers who fulfill employment, academic, and family obligations. The mother's educational and work efforts provide the necessary information, needed skills, and a desirable attitude for a family's general well-being. The study intends explicitly to 1. explore the experiences and challenges faced by working student mothers. 2. Investigate their coping strategies and aspirations for managing different roles. 3. understand their current living situation. The participants consisted of twelve (12) mothers who had a minimum of two dependents, were enrolled in a master's degree program, and were employed in an organization. Participants were administered a brief demographic questionnaire and engaged in a semi-structured interview. This study utilized interpretative phenomenology analysis. The latest findings emphasize that participants shared their experience of navigating the complexities of managing coursework, jobs, and caregiving responsibilities, which led to feeling overwhelmed. The stress factor was primarily attributed to low income and inadequate childcare expenses. However, they employed effective coping strategies using work-life balance, such as social support and time management. Pursuing a master's degree encompassed the opportunity to enhance their abilities and expand their knowledge and earning potential. The study revealed that they exhibited strong motivation and perseverance, with solid career aspirations driving their academic and professional pursuits, benefiting themselves and their families.